HUBUNGAN TIPE KEPRIBADIAN DENGAN KEJADIAN DEPRESI LANSIA DI PANTI WERDHA GAU MABAJI - sukurni Sukurni; Saida Saida; La Ode Alifariki; tukatman tukatman (NHM PRESS, 2021)
Depression is a mental disorder in the mood. Personality can change a person in certain conditions and circumstances, including the elderly who are in social institutions. Therefore, to determine the incidence of depression in the elderly, it is necessary to know the type of personality which is one of the factors causing depression in the elderly. This study aims to determine the relationship between personality types and the incidence of depression in the elderly in Tresna Werdha Gau Mabaji Gowa social institution. The population in this study were the elderly who live at the Tresna Werdha Gau Mabaji Gowa social institution with a total sample of 30 people. Data processing used SPSS 16 with the chi-square test. The results showed that the elderly who had the personality type with the highest percentage was the ambivert personality type as many as 28 people (93.3%), and the lowest personality type was the introvert as many as 2 people (6.7%). Elderly at the Tresna Werdha Gau Mabaji Gowa social institution, most of them did not experience depression, as many as 27 people (90%), and the lowest was depression 3 people (10%). The ambivert personality type with no depression was 27 people (90%), while the ambivert personality type with the incidence of depression was 1 person (3.3%), the introvert personality type with the incidence of depression was 2 people (6.7%). p = 0.07, which means <0.05, the conclusion of this study is that there is no relationship between personality type and the incidence of depression in the elderly